Peran Humas Dalam Membangun Citra Pemerintahan Sumatera Utara Pada Kantor Biro Humas Gubernur - Syahputra, Dolly Indra; Hendra, Yan; Hidayat, Taufik Wal (PERSPEKTIF, 2018)
Thisresearchismotivatedbytheimportance ofpublic relationsroleinbuildingthe imageofgovernment.Thepurposeofthisstudy istoexplaintheroleof publicrelationsin buildingtheimageofthegovernmentofNorthSumatra.Theoriesusedinthisstudyinclude the theoryofcommunication,public relationsandthe theory ofimage. The type ofthis research isqualitative research usingqualitativedecriptive method,Researchdatacollected byinterviewing someresource. Resourcepersonsofthisresearcharepersonnelinpublic relationsdepartmentof North ?Sumatera ?such ?as ?public ?relations? sub-chairman ?and ?four ?public ?relations? staff, researchresultshowsthatpublicrelationsrole inbuildingimageofNorthSumateraisseen frompublic relationsrole asexpertadvisor,public relationsroleasproblem solver,public relationsrole ascommunicationfacilitator.Overallitcanbeexplainedthatthe public relationsof NorthSumatragovernmenthasdoneitsrolein building theimageofNorth Sumatera government.?